The Influence of the Institutions on Entrepreneurship Development: Public Support and Perception of Entrepreneurship Development in the Czech Republic - Petr Hlaváček; Marta Zambochova; Tomas Sivicek (Amfiteatru Economic Journal, 2015)
This article deals with the research of entrepreneurship development in the frame of institutional environment in the Czech Republic. The example of the Czech Republic shows similar problems and specifics of post-transformation economies in Central and Eastern Europe. The goal is to discover the impact of specific institutional barriers on entrepreneurship development from the perspective of entrepreneurs and willingness to start own business. The surveys revealed that institutional barriers have significant impact on business. The influence of public administration and the configuration of the legislative environment are other key factors. Entrepreneurship policies should be more effective and public administration needs to create a better system of support and information transfer for new entrepreneurs and entrepreneurship development.
Keywords: D70; H70; O43; O52; 330; entrepreneurship; institutional environment; barriers; development; public support; Czech Republic